‘ABD AL-QĀDIR AL-JĪLĀNĪ’S SUFISM: A SPIRITUAL RESPONSE TO MODERN CRISES OF MEANING - Kasmuri; Agus Riyadi; Awaludin Pimay; Isma. Ae. Lijea (UIN Raden Mas Said Surakarta, 2025)
The spiritual crisis of modern society arises from the loss of divine vision caused by modern lifestyles. Sufism, as an alternative, offers an approach to address this issue. This study analyzes the concept of Sufism by Al-Jīlānī and its relevance in dealing with the spiritual crisis. Using a qualitative method with a literature study approach, this research collects data through literature review and documentation. The findings show that Sufism by ‘Abd al-Qādir al-Jīlānī consists of stages including repentance, asceticism, piety, trust in God, patience, contentment, gratitude, poverty, sincerity, love, and knowledge of God. These stages provide solutions to the spiritual crisis and function as self-control in facing the negative influences of modern society. The application of ‘Abd al-Qādir al-Jīlānī’s concept of Sufism is relevant as a response to three clusters of issues in contemporary society: spiritual, psychological, and social. This study also highlights the need for further research to evaluate the effectiveness of Sufism in addressing the spiritual crisis. The unique contribution of this research is its emphasis on the relevance of the Sufi concept in the context of modern society and its potential application to improve the fragmented spiritual condition.